2019
DOI: 10.4236/jbm.2019.75017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preoperative Dutasteride on Bleeding Related to Transurethral Resection of Prostate in Patients with Benign Prostatic Hyperplasia

Abstract: Background: Transurethral resection of prostate (TURP) is the gold standard in the surgical treatment of symptomatic benign prostatic hyperplasia (BPH). Blood loss is one of the most common complications of TURP. Objective: To evaluate the effect of preoperative dutasteride on bleeding related to TURP in patients with BPH. Materials and Methods: This prospective interventional study was done in the department of urology, Dhaka Medical College Hospital, Dhaka, Bangladesh during the period of July 2016 to June 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The rich blood flow in the prostate gland and the high intraoperative bleeding are risks of conventional TURP (25). This study found that blood loss after TUSP was significantly lower in BPH patients with a prostate volume less than 50 mL than those with more than 50 mL.…”
Section: Discussionmentioning
confidence: 57%
“…The rich blood flow in the prostate gland and the high intraoperative bleeding are risks of conventional TURP (25). This study found that blood loss after TUSP was significantly lower in BPH patients with a prostate volume less than 50 mL than those with more than 50 mL.…”
Section: Discussionmentioning
confidence: 57%
“…An initial 516 titles and abstracts were screened, of which 32 studies were accessed for full-text eligibility. In all, 11 were included for meta-analysis [ 19 , 20 , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] ]. Table 1 presented the summary of the included studies, while Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies (775 samples) from both treatment ( n =387) and control ( n =388) groups reported the Hb level alteration before and after the procedure [ [25] , [26] , [27] , [29] , [30] , [31] ]. Pooled analysis showed a significant lower reduction of Hb level in group receiving dutasteride as compared with control (MD −1.10, 95% CI −1.39 to −0.81, p <0.00001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If intraoperative insertion, exit, rotation of the mirror sheath caused some damage to the urethra, increase the risk of surgery [10] . If the lithotripsy time is prolonged, it is easy to cause bladder mucosa edema and brittleness, which increases the risk of intraoperative bladder perforation and postoperative infection [11] . In particular, for patients with cardiopulmonary basic diseases, the extension of operation time will increase the risk of operation.…”
mentioning
confidence: 99%